'Books that Irish people ought to read' - Tynan, Katharine, 1861-1931
Katharine Tynan refers to poetry, song and prose, and diverse figures including Maria Edgeworth, George Sigerson, Douglas Hyde, Jonathan Swift, George Darley, John Mitchel, Thomas Davis, William Carleton, John Millington Synge, Charles Kickham, Somerville and Ross, among many others.
On the verso of page 29 is a further manuscript page.
Keywords: Irish literature; Irish poetry; Ireland